A Study on Internal Auditor Perceptions of the Function Ability to Add Value. (21st September 2015) - D'Onza, Giuseppe; Selim, Georges M.; Melville, Rob; Allegrini, Marco
<x xml:space="preserve">Abstract</x> In the context of internal auditing, when there is no obvious correlation between auditors' activities and financial performance, it is critical to identify areas where value is added as well as the drivers that enable this, in the evaluation of the effectiveness of the internal auditing function (IAF). This paper addresses whether and how internal auditing activities (IAAs) can add value to their organisations. In order to gain some understanding of value‐adding processes, we analysed the responses of more than 1, 800 internal auditors to questions specifically designed to evaluate this contribution. This sample was based on the 2010 global survey of the internal auditing profession that the Institute of Internal Auditors Research Foundation (IIARF) carried out; only those respondents were included whose role showed they were in a position to make decisions and influence the work of their IAF. This study found evidence that four variables are positively associated with adding value: IAF independence and objectivity; compliance with the Institute of Internal Auditors' (IIA) Code of Ethics; the IAF's contribution to the evaluation of the effectiveness of internal control; and the IAF's contribution to the evaluation of the effectiveness of risk management. With the exception of independence and objectivity, the analysis reveals that the remaining value drivers of the IAF's activities vary between developed and emerging countries and between financial and non‐financial companies, suggesting that the factors influencing the IAAs' effectiveness might be partially context dependent.